The Effect Of Entrepreneurship Training On Community Empowerment Levels In The Forum Komunitas UMKM Cisayong - Syifa Fadillah; Mira Nurfitriya; Nizza Nadya Rachmani (SEAN Institute, 2024)
Empowerment is a process aimed at strengthening and enhancing the capabilities of individuals or vulnerable community groups so that they can independently identify needs, analyze potential, and determine the best solutions. However, community empowerment in the Forum Komunitas UMKM Cisayong has not been optimal, primarily due to low member participation in training sessions that only partially meet their needs. This study seeks to present an overview of entrepreneurship training and the extent of community empowerment and evaluate its impact on the level of community empowerment within the Forum Komunitas UMKM Cisayong. The research utilizes a quantitative method with both descriptive and verificative approaches. The study's population consists of 84 respondents, with a sample of 30 respondents selected through purposive sampling techniques. Data analysis was performed using simple linear regression in SPSS version 29, encompassing validity and reliability tests, classical assumption tests, and the regression analysis. The study's findings indicate a significant relationship between entrepreneurship training and community empowerment, with a coefficient of determination of 37,2%. This study concludes that entrepreneurship training positively and significantly enhances community empowerment within the Forum Komunitas UMKM Cisayong.